Sintilimab Combined with Lenvatinib for Advanced Intrahepatic Cholangiocarcinoma in Second-Line Setting—A Multi-Center Observational Study - Ding, Xiaoyan; Li, Guangxin; Sun, Wei; Shen, Yanjun; Teng, Ying; Xu, Yawen; Li, Wendong; Liu, Mei; Chen, Jinglong (Frontiers in Oncology, 2022)
Background: Patients with advanced intrahepatic cholangiocarcinoma (iCCA) have a poor prognosis and a substantial unmet clinical need. The study was aimed to investigate the efficacy and safety of Sintilimab combined with Lenvatinib for advanced iCCA in second-line setting. Methods: The patients at multiple centers, who progressed after the first-line chemotherapy or could not tolerate chemotherapy, were treated with the combination of Sintilimab plus Lenvatinib. The primary end point was time to progression (TTP), and the secondary end points included tumor objective response rate (ORR), disease control rate (DCR), overall survival (OS) and toxicity. Prognostic factors were analyzed using cox-regression analysis. Results: A total of 41 patients with advanced iCCA were enrolled for this multi-center observational study. Under a median follow-up of 12.1 months, the median age was 59y (range: 33-75y). Sixteen patients died of disease progression, with a median TTP of 6.6 months (95% CI: 4.9-8.3). ORR and DCR were 46.3% and 70.3%, respectively. The patients with PD-L1 TPS ≥10% reported a significantly higher ORR compared to those with PD-L1 TPS <10%, 93.8% (15/16) vs 16.0% (4/25), P<0.001. The median TTP was significantly improved in patients with PD-L1 TPS ≥10%, 16.9 months (95% CI: 7.5-26.3) vs 4.1 months (95% CI: 1.8-6.4), P=0.001. Attaining treatment response predicts favorable TTP in a multivariate Cox model. Treatment-emergent adverse events occurred with 70.3% probability. And no treatment-related death had been reported. Conclusion: The combination of Sintilimab plus Lenvatinib is effective and well tolerated for advanced iCCA in the second-line setting. PD-L1 TPS expression may predict the efficacy of the combination therapy. Further investigation is warranted to investigate this combination regimen in advanced iCCA.